PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN NON PERFORMING LOAN (NPL) TERHADAP RETURN ON ASSET (ROA) PADA BANK UMUM SWASTA NASIONAL YANG TERDAFTAR PADA OTORITAS JASA KEUANGAN (Periode 2016-2021) - A’qilia Munawarah; Siti Rusidah; Rizky Muslim Hidayat (Smart Business Journal (SBJ), 2023)
The overarching goals of this study are to (1) investigate the partial and simultaneous each variable at National Private Commercial Banks (BUSN) licensed by the Financial Services Authority (OJK), and (2) apply the study's findings to a sample of BUSN (2016-2021 period). This study employs a causal-associational approach to quantitative research. The data used to create this summary was collected using a kind of sampling known as "Purposeful Sampling," which was applied to a subset of BUSN Bank's financial records at random. Each state-owned enterprise bank's financial statements from 2016-2021 were used as secondary data in this analysis. To evaluate the business's success, these statements were used. Reading books and financial reports, in addition to checking out the Financial Services Authority's website. In this study, using Multiple Linear Regression Analysis with the 26.0 Version of SPSS. The findings revealed that the Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) had only a minimal impact on ROA (ROA). The Capital Adequacy Ratio (CAR) and Non-Performing Loans are known to have a significant impact on the Return On Assets (ROA) figure (22.90%),